Short Communication Claisen Rearrangement of 2'-Hydroxy-4-Methyl-4'-Prenyloxychalcone (Biological Sciences - PJSIR, 2007)
. Clai sen rearran gement of 2'-hydroxy -4-methyl-4'-prenyloxychalcone (2) using acetic anhydride i n di methylaniline yields four major compound s vi z. 2'-hydroxy-4-methyl-4", 4", 5"-trimethyldi hydrofurano (2", 3": 4' , 3')ch a lcone (3), 2',4'-diacetoxy-4-methyl-3' -(a, a-dimethy l allyl)chal cone (4), 2', 4' -diacetoxy-4-methy l-5'-(a, a -dimethylal l yl)chalcone (5), 2',4'-d i acetoxy-4-methyl chalcone (6) and severa l oth er mi nor compounds. All the i sol ated products were identified on the basis of !R, UV, ' H-N M R , Mass and Elemen tal anal ysi s.